2017
DOI: 10.1002/slct.201702277
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dimeric Imidazo[1, 5‐a]pyridines and Their Photophysical Properties

Abstract: We designed and synthesized dimeric imidazo[1, 5-a]pyridines possessing various aryl groups at 1,1'-positions. The solution of these derivatives exhibited fluorescence emission in wavelength range of 487-512 nm. The fluorescence emissions were slightly red-shifted under acidic condition by addition of trifluoroacetic acid. Furthermore, the original fluorescence spectra were observed after the addition of triethylamine as a base.[a] Prof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Other different applications have been reported for multi‐ impy products such as bioimaging or therapeutic agents under UVA‐LED irradiation conditions [86–88] . In this case, the tested products show a potential application as photodynamic therapy agents against tumour cells (F. Yagishita et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other different applications have been reported for multi‐ impy products such as bioimaging or therapeutic agents under UVA‐LED irradiation conditions [86–88] . In this case, the tested products show a potential application as photodynamic therapy agents against tumour cells (F. Yagishita et al.…”
Section: Discussionmentioning
confidence: 99%
“…Other different applications have been reported for multiimpy products such as bioimaging or therapeutic agents under UVA-LED irradiation conditions. [86][87][88] In this case, the tested products show a potential application as photodynamic therapy agents against tumour cells (F. Yagishita et al reported the use of UVA-LED λexc = 365 nm, 1.1 W as a light source). [86] In general, a multi-impy nucleus has been successfully prepared [89,90] showing similar chelating behaviours in compar-ison to the most investigated poly-pyridines or multibipyridines.…”
Section: Multi-impy Skeletonmentioning
confidence: 99%
“…All compounds were synthetized following the literature procedures. 21,23,36,[51][52][53][54] A list of the solvents employed for crystallization and the conditions of synthesis of each polymorph can be found in Table 1.…”
Section: Synthesismentioning
confidence: 99%
“…N-Heteroacenes are capable of recognizing Brønsteda cids through the lone-pair electrons of the imino Natoms, which are characteristic of Lewis-basic sp 2 -hybridized orbitals. [18][19][20][21][22][23] We previously reportedt hat a p-conjugated liquid that was composed of an N-heteroacene framework respondedt oH Cl vapor,t hereby resultingi nad ramatic change in the color of its photoluminescence. [15] Herein, we report the synthesis of an ew stimuli-responsive p-conjugated liquid (1) that was composed of an N-heteroacene framework with finely tuned electronic properties as well as acid-responsive capabilities.…”
Section: Introductionmentioning
confidence: 98%
“…With the aim of developing a series of new functional fluidic liquids, we focused on the N‐heteroacene framework, in which C atoms in a π‐conjugated hydrocarbon are partially replaced by imino N atoms. N‐Heteroacenes are capable of recognizing Brønsted acids through the lone‐pair electrons of the imino N atoms, which are characteristic of Lewis‐basic sp 2 ‐hybridized orbitals . We previously reported that a π‐conjugated liquid that was composed of an N‐heteroacene framework responded to HCl vapor, thereby resulting in a dramatic change in the color of its photoluminescence .…”
Section: Introductionmentioning
confidence: 99%